Originality and Utilitarian Works: The Uneasy Relationship between Copyright Law and Unfair Competition - Scassa, Teresa (Université d'Ottawa | University of Ottawa, 2004)
Courts have struggled with articulating the standard for “originality” in copyright law. Some judges have leaned towards a “sweat of the brow” theory, that rewards authors for their investment of labour in creating a work. Others, most notably, the U.S. Supreme Court in the landmark decision of Feist Publications Inc. v. Rural Telephone Service Co. Inc., have held out for a standard which requires some “spark” or modicum of creativity. In this article, the author examines the concept of “originality” in light of the shifting purposes of copyright law in Canada, and the historical relationship of utilitarian works to copyright law. Works such as directories and factual compilations owe their value not to their contents, which are often in the public domain, but to the effort that has gone into collecting those contents. The scope of protection of such “utilitarian works” to be offered under copyright law has generated controversy in case law and commentary. By examining the treatment of the concept of “originality” in recent Canadian cases dealing with utilitarian works, the author explores the uneasy relationship between unfair competition law and copyright law in Canada. She argues that the proliferation of utilitarian works protected by copyright, and in particular, information products, has rendered a threshold for originality extremely problematic. She argues that the problem lies in the tension between copyright and unfair competition, primarily in relation to utilitarian works. Copyright, she concludes, is an inapt vehicle for resolving issues of competition in the information economy.
Keywords: compilations; unfair competition; public domain; intellectual property; copyright